Pubertal development and prostate cancer risk: Mendelian randomization study in a population-based cohort. Issue 1 (December 2016) - Bonilla, Carolina; Lewis, Sarah; Martin, Richard; Donovan, Jenny; Hamdy, Freddie; Neal, David; Eeles, Rosalind; Easton, Doug; Kote-Jarai, Zsofia; Al Olama, Ali; Benlloch, Sara; Muir, Kenneth; et al.
Abstract Background Epidemiological studies have observed a positive association between an earlier age at sexual development and prostate cancer, but markers of sexual maturation in boys are imprecise and observational estimates are likely to suffer from a degree of uncontrolled confounding. To obtain causal estimates, we examined the role of pubertal development in prostate cancer using genetic polymorphisms associated with Tanner stage in adolescent boys in a Mendelian randomization (MR) approach. Methods We derived a weighted genetic risk score for pubertal development, combining 13 SNPs associated with male Tanner stage. A higher score indicated a later puberty onset. We examined the association of this score with prostate cancer risk, stage and grade in the UK-based ProtecT case-control study (n  = 2, 927), and used the PRACTICAL consortium (n  = 43, 737) as a replication sample. Results In ProtecT, the puberty genetic score was inversely associated with prostate cancer grade (odds ratio (OR) of high- vs. low-grade cancer, per tertile of the score: 0.76; 95 % CI, 0.64–0.89). In an instrumental variable estimation of the causal OR, later physical development in adolescence (equivalent to a difference of one Tanner stage between pubertal boys of the same age) was associated with a 77 % (95 % CI, 43–91 %) reduced odds of high Gleason prostate cancer. In PRACTICAL, the puberty genetic score was associated with prostate cancer stage (OR of advanced vs. localized cancer, per tertile: 0.95; 95 % CI, 0.91–1.00) and prostate cancer-specific mortality (hazard ratio amongst cases, per tertile: 0.94; 95 % CI, 0.90–0.98), but not with disease grade. Conclusions Older age at sexual maturation is causally linked to a reduced risk of later prostate cancer, especially aggressive disease.